Cumulative defect structures for experimentally attainable low thermal conductivity in thermoelectric (Bi, Sb)2Te3 alloys. (September 2021) - Lee, K.H.; Kim, Y.-M.; Park, C.O.; Shin, W.H.; Kim, S.W.; Kim, H.-S.; Kim, S.-i.
Abstract: Manipulation of thermal transport properties by defect engineering is an important but yet unresolved issue in thermoelectrics, since rational design strategies of multiple defect structures for minimizing lattice thermal conductivity are lacking. The key is to comprehend complex interaction between different frequency-dependent phonon scattering processes by multiple defect structures. Herein, individual contributions in lattice thermal conductivity reduction from each defect structure—point defects (0-dimensional, 0D), dislocations (1D), grain boundaries (2D), and nanoparticles (3D)—are characterized based on experimental results of commercial (Bi, Sb)2 Te3 -based alloys fitted to Debye-Callaway model. Then, the cumulative contributions by multiple defect structures are investigated interactively by estimating total phonon relaxation time. Therefore, the interactive role of multiple defect structures in reducing lattice thermal conductivity is elucidated. To extend the approach to other thermoelectric materials, PbTe-based alloys with multiple defect structures of point defects and grain boundaries were modeled as well. This approach enables to provide a thorough design of defect structures for realizing the experimentally attainable low lattice thermal conductivity in thermoelectric materials. Graphical abstract: Image 1 Highlights: Contributions in thermal conductivity reduction by individual defects are investigated. Cumulative contributions by multiple defect structures are interactively investigated. The interactive role of multiple defect structures in reducing thermal conductivity is elucidated. This approach enables to provide a thorough design of multiple defect structures. This enables to realize experimentally attainable low lattice thermal conductivity.